A room temperature reversible hydrogen storage high entropy alloy with understoichiometric magnesium-containing C15 structure Laves phase and preparation method thereof

By designing and preparing a Laves phase room temperature reversible hydrogen storage high-entropy alloy with understoichiometric magnesium-containing C15 structure, the problem of insufficient performance of existing hydrogen storage alloys is solved, and the effects of high hydrogen storage capacity, fast reversible hydrogen storage and low cost density are achieved.

CN116516229BActive Publication Date: 2025-03-25ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310503013.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-03-25
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

The existing hydrogen storage alloys have problems such as low hydrogen storage capacity, poor circulation performance, high hydrogen release temperature and poor kinetic performance. The preparation of magnesium-containing Laves hydrogen storage high-entropy alloys is difficult to prepare, which affects the material performance.

Method used

A high-entropy alloy with a C15 structure understood stoichiometric magnesium-containing Laves phase reversible hydrogen storage room temperature was designed, and raw materials were prepared by the molecular formula of Zr0.85Ti0.15MgxNi1.2Mn0.56V0.12Fe0.12 alloy, the alloy precursor was prepared by arc smelting and mechanical crushing, and a high-entropy alloy with a single-phase structure of C15 Laves was obtained by sintering.

Benefits of technology

The C15 Laves single-phase structure preparation of high-entropy alloys has the characteristics of room temperature hydrogen storage capacity of 0.3 to 1.0 wt.% and room temperature rapid reversible hydrogen storage, which reduces the cost and density of the alloy and is easy to activate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516229B_ABST
    Figure CN116516229B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of hydrogen storage materials, and specifically relates to a room temperature reversible hydrogen storage high entropy alloy containing a C15 structure Laves phase and a preparation method thereof. The chemical formula of the material is Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 (x=0.2-0.4). The preparation process of the hydrogen storage high entropy alloy is to firstly refine Zr by arc melting. 0.85 Ti 0.15 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 The precursor is crushed and mixed with Mg powder, and then the mixed sample is sintered to obtain a high entropy alloy. The preparation method is simple and easy to control, and can accurately control the composition of the magnesium-containing high entropy alloy. The alloy does not contain rare earth elements, and only contains a small amount of V element, and the added Mg content can reach 12%, which greatly reduces the cost and density of the alloy. The substoichiometric hydrogen storage high entropy alloy prepared by the present invention has a C15Laves single-phase structure, a hydrogen storage capacity of 0.3 to 1.0wt.% at room temperature, and has the characteristics of rapid reversible hydrogen storage at room temperature and easy activation. Compared with other high entropy alloys, the alloy provided by the present invention has a C15Laves single-phase structure and an outstanding effect of rapid reversible hydrogen absorption and desorption at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen storage materials, and in particular relates to a room temperature reversible hydrogen storage high entropy alloy containing C15 structure Laves phase and under-stoichiometric magnesium and a preparation method thereof. Background Art

[0002] Nowadays, energy crisis and environmental crisis force people to develop and utilize clean energy. Among them, hydrogen energy is considered to be an ideal carrier of renewable energy because of its advantages such as cleanliness, high efficiency, environmental protection and sustainable utilization. However, the development of the hydrogen energy industry is still limited by the lack of efficient and safe hydrogen storage methods. Compared with liquid hydrogen storage and gaseous hydrogen storage, solid hydrogen storage has been widely studied because of its advantages such as high energy density and safety, low cost and convenient transportation. At present, the types of hydrogen storage alloys mainly include rare earth series, titanium iron series, zirconium series, vanadium series and magnesium series. Among them, rare earth hydrogen storage alloys have low hydrogen storage capacity, high cost and poor cycle performance; titanium iron series hydrogen storage alloys have Laves phase crystal structure, which makes this type of alloy have the advantages of high hydrogen storage capacity and long cycle life, but activation is more difficult; zirconium series hydrogen storage alloys have high hydrogen desorption temperature; although vanadium series and magnesium series hydrogen storage alloys have high hydrogen storage capacity, they also have problems such as too high hydrogen desorption temperature and poor kinetic performance. Therefore, it is still necessary to explore new hydrogen storage alloys, and the emergence of high entropy alloys may provide new ideas for the research of new hydrogen storage materials.

[0003] High entropy alloys are composed of five or more elements, including high entropy effect, cocktail effect, lattice distortion effect and hysteresis diffusion effect, and these four effects all play a certain role in obtaining hydrogen storage alloys with excellent hydrogen storage performance. Among them, the high entropy effect provides certain conditions for the formation of single-phase solid solution in high entropy alloys; the difference in atomic radius causes serious lattice distortion, which leads to more lattice gaps, defects and strains in the alloy, thus providing more vacancies and channels, which is conducive to the diffusion, dissociation and recombination of hydrogen atoms; the hysteresis diffusion effect provides the basis for high entropy alloys to have good hydrogen storage capacity; at the same time, under the influence of the cocktail effect, all the main elements jointly affect the alloy performance. Due to the diversity of element selection and the controllability of element ratios, it is possible to prepare high entropy alloys with comprehensive performance that meets the needs of hydrogen storage applications.

[0004] In recent years, domestic and foreign researchers have been studying more and more on the hydrogen storage properties of high entropy alloys. Among them, intermetallic high entropy alloys have been widely studied because of their high hydrogen storage capacity, good low-temperature hydrogen desorption performance, and good hydrogen absorption and desorption kinetics. For example, AB2-type TiZrCrMnFeNi high entropy alloy has a room temperature reversible hydrogen storage capacity of 1.6wt.% [P Edalati, RFloriano, A Mohammadi, et al. Scripta Materialia, 2020, 178: 387-390.]; AB2-type TiZrFeMnCrV high entropy alloy still has a hydrogen storage capacity of about 1.76wt.% after 50 cycles [J Chen, Z Li, H Huang, et al. Scripta Materialia, 2022, 212: 114548.]. In addition, studies have shown that designing different A / B-type intermetallic high-entropy alloys has the potential to improve the hydrogen storage performance of alloys. For example, at 473K, the A3B2-type TiZrNbCrFe high-entropy alloy with C14 Laves phase as the main phase even has a reversible hydrogen storage capacity of 1.9wt.% [R Floriano, GZepon, K Edalati, et al. International Journal of Hydrogen Energy, 2021, 46(46): 23757-23766.]. However, the intermetallic high entropy alloys studied so far all have C14 Laves phase as the main phase, but the C15 Laves phase crystal structure has a higher stacking fault density than the C14 Laves phase crystal structure. This defect structure can make the alloy show better hydrogen storage performance, such as Young et al. [K. Young, T. Ouchi, B. Huang, et al. Journal of Alloys and Compounds. 2010, 506 (2): 841-848] found that compared with the alloy with C14 Laves phase as the main phase, the alloy with C15 Laves phase as the main phase has better performance in hydrogen storage capacity, reversible hydrogen storage capacity, high-discharge performance, hydrogen diffusion, and low-temperature performance. Therefore, the design of an intermetallic high entropy alloy with C15 Laves phase as the main phase may show more excellent hydrogen storage performance.

[0005] In addition, non-stoichiometric composition design is also one of the means to improve the hydrogen storage performance of intermetallic compounds. This is attributed to the following aspects: on the one hand, compared with alloys with strict stoichiometric composition, non-stoichiometric alloys usually have higher defect density; on the other hand, the use of non-stoichiometric methods can change the atomic ratio and atomic occupancy in the unit cell, thereby achieving the effect of regulating the chemical environment of the tetrahedral gap and the unit cell volume. These changes in microstructure will bring about great changes to the hydrogen storage performance of the alloy. For example: relative to the stoichiometric YFe 1.5 Al 0.5 For alloys, the substoichiometric YFe 1.5 Al 0.5-x (x=0.1,0.2) The hydrogenation capacity and hydrogen absorption rate of the alloy are improved, and its reversible capacity is larger [Z Li, H Wang, L Ouyang, et al. Journal of Alloys and Compounds, 2017, 704: 491-498.]. In addition, because metal Mg has the advantages of high hydrogen storage capacity, low density, wide source and low cost, adding Mg to Laves phase intermetallic high entropy alloy can better reduce the density of the alloy and has the possibility of further improving the hydrogen storage capacity. However, there are few studies on magnesium-containing Laves phase hydrogen storage high entropy alloys in domestic and foreign literature. This may be related to the preparation of magnesium-containing Laves phase hydrogen storage high entropy alloys: the traditional smelting method cannot accurately prepare magnesium-containing Laves phase hydrogen storage high entropy alloys because Mg has a low melting and boiling point, and it is also difficult to prepare high-purity Laves phase magnesium-containing hydrogen storage high entropy alloys by mechanical alloying, which leads to the deterioration of material properties.

[0006] In view of this, how to design and prepare a substoichiometric magnesium-containing C15 structure Laves phase room temperature reversible hydrogen storage high entropy alloy has important practical application value. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems existing in the conventional technology, and to design a room temperature reversible hydrogen storage high entropy alloy with a Laves phase structure and a magnesium-containing C15 structure understoichiometric, and to develop a corresponding preparation method. 0.85 Ti 0.15 Ni 1. 2Mn 0.56 V 0.12 Fe 0.12 The raw materials were prepared according to the alloy molecular formula, and then the alloy precursor was prepared by arc melting; 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V0.12 Fe 0.12 (x=0.2~0.4) alloy molecular formula The mechanically crushed precursor is weighed and manually mixed with Mg powder; then the mixed sample is sintered to obtain a room temperature reversible hydrogen storage high entropy alloy with a C15 structure Laves phase containing less stoichiometric magnesium. The present invention prepares a less stoichiometric magnesium-containing hydrogen storage high entropy alloy, which has a C15 Laves single-phase structure, and B / A=1.4~1.7, the alloy does not contain rare earth elements, and the added Mg content can reach 12%, which greatly reduces the cost and density of the alloy; in addition, the less stoichiometric magnesium-containing C15 structure Laves phase hydrogen storage high entropy alloy has a hydrogen storage capacity of 0.3~1.0wt.% at room temperature, and has the characteristics of rapid reversible hydrogen storage at room temperature and easy activation.

[0008] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0009] The present invention provides a room temperature reversible hydrogen storage high entropy alloy containing a C15 structure Laves phase and a magnesium-containing understoichiometric amount, wherein the chemical formula of the material is Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 , where x=0.2~0.4, B / A=1.4~1.7, type A elements include Zr, Ti and Mg, and type B elements include Ni, Mn, V and Fe.

[0010] The present invention also provides a method for preparing a room temperature reversible hydrogen storage high entropy alloy with a Laves phase having a stoichiometric magnesium-containing C15 structure, comprising the following steps:

[0011] 1) Press Zr first 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy molecular formula Weigh a certain amount of zirconium block, titanium block, vanadium block, iron block, nickel sheet and manganese sheet; in an argon atmosphere, spread the above metal raw materials from bottom to top in the crucible according to the melting point from low to high, and then -2 The alloy is completely melted and cooled to form an alloy ingot. The alloy ingot is turned over and repeatedly melted 3 to 4 times to obtain a precursor sample of a hydrogen storage high entropy alloy.

[0012] 2) In a glove box, the obtained precursor sample was mechanically crushed into a precursor powder of 100-300 mesh using a stainless steel mortar;

[0013] 3) Press Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy formula The precursor powder and Mg powder were weighed and mixed evenly manually in a glove box;

[0014] 4) Weigh a certain amount of the mixed sample using an analytical balance in a glove box, and press it into a tablet with a diameter of 10 to 15 mm using a powder tablet press;

[0015] 5) placing the pressed sheet in a stainless steel sealed container in a glove box and filling it with argon gas at a pressure of 0.2 to 0.4 MPa; then placing it in an annealing furnace for sintering, and after sintering, cooling it to room temperature with the furnace and taking it out to finally obtain a room temperature reversible hydrogen storage high entropy alloy with a stoichiometric magnesium-containing C15 structure Laves phase.

[0016] Furthermore, in step 1), the purity of the zirconium block is ≥99.7%, the purity of the titanium block is ≥99.9%, the purity of the vanadium block is ≥99.9%, the purity of the iron block is ≥99.9%, the purity of the nickel sheet is ≥99.5%, and the purity of the manganese sheet is ≥99.5%.

[0017] Furthermore, in step 1), considering the burning of titanium blocks and manganese sheets during the arc melting process, 2 wt.% of titanium blocks and 5 wt.% of manganese sheets are additionally added.

[0018] Furthermore, in step 3), the purity of the Mg powder is ≥ 99.5%.

[0019] Furthermore, in step 3), 20 wt.% of Mg powder is additionally added to compensate for the burning loss of Mg powder in the subsequent sintering process.

[0020] Furthermore, in step 5), the sintering temperature of the sintering process is 750-850° C., and the time is 12-48 hours.

[0021] The present invention also provides an application of a room temperature reversible hydrogen storage high entropy alloy with a C15 structure and a magnesium-containing understoichiometric structure, and the alloy comprises a high entropy alloy having a C15 structure and a magnesium-containing structure, and a hydrogen storage structure. Before utilizing the hydrogen storage function of the high entropy alloy, the alloy is subjected to 1-2 cycles of hydrogen absorption and desorption at a temperature of 250° C. and a pressure of 3.5 MPa to obtain the activity of the hydrogen storage high entropy alloy, and then the alloy can be used for hydrogen storage.

[0022] The principle of the present invention is: in Zr 0.85 Ti 0.15 Ni 1.2 Mn 0.56 V 0.12Fe 0.12 On the basis of high entropy alloy, the hydrogen storage performance of the alloy is further improved by adding the light element Mg, which can be attributed to the following two aspects: on the one hand, the addition of the light element Mg significantly reduces the density of the alloy, thereby increasing the hydrogen storage capacity of the alloy; on the other hand, the addition of Mg changes the stoichiometric ratio of the alloy, thereby forming a substoichiometric hydrogen storage high entropy alloy, which leads to vacancies in the positions occupied by the B-side atoms in the alloy, and is occupied by some A-side atoms, so that the alloy produces defect structures such as dislocations, twins and stacking faults that are beneficial to improving the hydrogen storage performance of the alloy. In addition, there are large differences in atomic radius and electronegativity in the hydrogen storage high entropy alloy, which leads to more lattice gaps, defects and strains in the alloy, while weakening the bond energy in the alloy, thereby promoting the diffusion, dissociation and recombination of hydrogen atoms.

[0023] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0024] 1. The present invention designs a room temperature reversible high entropy alloy with a C15 Laves structure containing magnesium and a substoichiometric hydrogen storage high entropy alloy, and develops a corresponding preparation method. The preparation method is relatively simple and easy to control, and can overcome the problems that the composition of the magnesium-containing high entropy alloy is difficult to control during the preparation process, and the alloy is composed of multiple phases, so that the composition and phase purity of the magnesium-containing high entropy alloy can be accurately controlled, and finally a substoichiometric magnesium-containing hydrogen storage high entropy alloy with a C15 Laves single-phase structure can be accurately prepared.

[0025] 2. The present invention successfully prepared a room temperature reversible hydrogen storage high entropy alloy with understoichiometric magnesium-containing C15 structure Laves phase, Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 The (x=0.2-0.4) alloy does not contain rare earth elements, and the added Mg content can reach 12%, which greatly reduces the cost and density of the alloy.

[0026] 3. Zr prepared by the present invention 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 High entropy alloys are easy to activate and can be fully activated by absorbing and releasing hydrogen 1 to 2 times at 250°C.

[0027] 4. Zr prepared by the present invention 0.85 Ti 0.15 Mg x Ni1.2 Mn 0.56 V 0.12 Fe 0.12 The high entropy alloy has the characteristics of rapid and reversible hydrogen storage at room temperature, can completely absorb hydrogen within 4 minutes at 303 K, and can completely release hydrogen within 5 minutes at 303 K. Compared with other high entropy alloys, the present invention has the outstanding effects of using high-purity C15 Laves phase as the main phase and reversible absorption and desorption of hydrogen at room temperature.

[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0030] Figure 1 Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 (x=0.2,0.3) High entropy alloy X-ray diffraction (XRD) test spectrum;

[0031] Figure 2 Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 (x=0.2,0.3) Isothermal hydrogen absorption kinetics curve of high entropy alloy at 303K;

[0032] Figure 3 Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 (x=0.2,0.3) Isothermal hydrogen desorption kinetics curve of high entropy alloy at 303K. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention provides a room temperature reversible hydrogen storage high entropy alloy with a Laves phase structure containing magnesium and a stoichiometric amount, the chemical formula of which is Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 , where x = 0.2 to 0.4, B / A = 1.4 to 1.7. The preparation process of the hydrogen storage high entropy alloy is to firstly refine Zr by arc melting 0.85 Ti 0.15 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 The precursor is crushed and mixed with Mg powder, and then the mixed sample is sintered to obtain a room temperature reversible hydrogen storage high entropy alloy containing C15 structure Laves phase of magnesium. The preparation method is simple and easy to control, and can accurately control the composition of the magnesium-containing high entropy alloy. The alloy does not contain rare earth elements, and only contains a small amount of V element, and the added Mg content can reach 12%, which greatly reduces the cost and density of the alloy. The understoichiometric hydrogen storage high entropy alloy prepared by the present invention has a C15 Laves single-phase structure, a hydrogen storage capacity of 0.3 to 1.0 wt.% (mass percentage) at room temperature, and has the characteristics of rapid reversible hydrogen storage at room temperature and easy activation. Compared with other high entropy alloys, the alloy provided by the present invention has a C15 Laves single-phase structure and an outstanding effect of rapid reversible hydrogen absorption and desorption at room temperature.

[0035] The relevant specific embodiments of the present invention are:

[0036] Example 1

[0037] Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 The specific preparation steps of high entropy alloy are as follows:

[0038] (1) Press Zr first 0.85 Ti 0.15 Ni 1.2 Mn0.56 V 0.12 Fe 0.12 Alloy molecular formula Weigh a certain amount of zirconium block (purity ≥ 99.7%), titanium block (purity ≥ 99.9%), vanadium block (purity ≥ 99.9%), iron block (purity ≥ 99.9%), nickel sheet (purity ≥ 99.5%) and manganese sheet (purity ≥ 99.5%), with a total mass of 30g; in an argon atmosphere, lay the above metal raw materials from bottom to top in a crucible according to the melting point from low to high, and then perform arc vacuum melting (vacuum degree of 3×10 -3 Pa), the alloy is completely melted and cooled to form an alloy ingot, the alloy ingot is turned over and smelted repeatedly for 4 times to obtain Zr 0.85 Ti 0.15 Ni 1. 2Mn 0.56 V 0.12 Fe 0.12 Precursor;

[0039] (2) In a glove box, the precursor was mechanically crushed into 200 mesh powder using a stainless steel mortar;

[0040] (3) Press Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy formula Weigh the precursor powder and Mg powder (purity ≥ 99.5%), mix them evenly manually in a glove box, weigh 20 g of the mixed sample using an analytical balance, and press it into a tablet with a diameter of 13 mm using a powder tablet press;

[0041] (4) The pressed sheet is placed in a stainless steel sealed container in a glove box and filled with argon gas at a pressure of 0.4 MPa; then the pressed sheet is placed in an annealing furnace and sintered for one day at a sintering temperature of 800°C. After the sintering is completed, the pressed sheet is cooled to room temperature with the furnace and then removed, thereby finally obtaining a room temperature reversible hydrogen storage high entropy alloy with a Laves phase structure containing understoichiometric magnesium and a C15 structure.

[0042] Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 High entropy alloys consist of a C15 Laves single phase (see Figure 1 :Zr 0.8 5Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V0.12 Fe 0.12 High entropy alloy X-ray diffraction (XRD) test spectrum). Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 High entropy alloys can absorb 0.3 wt.% hydrogen at 303 K (see Figure 2 :Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 The isothermal hydrogen absorption kinetics of high entropy alloys at 303K) and the complete dehydrogenation at 303K (see Figure 3 :Zr 0.85 Ti 0.15 Mg 0.2 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Isothermal hydrogen desorption kinetics curve of high entropy alloy at 303K), which indicates that the alloy has the property of reversible hydrogen storage.

[0043] Example 2

[0044] Zr 0.85 Ti 0.15 Mg 0.3 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 The specific preparation steps of high entropy alloy are as follows:

[0045] (1) Press Zr first 0.85 Ti 0.15 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy molecular formula Weigh a certain amount of zirconium block (purity ≥ 99.7%), titanium block (purity ≥ 99.9%), vanadium block (purity ≥ 99.9%), iron block (purity ≥ 99.9%), nickel sheet (purity ≥ 99.5%) and manganese sheet (purity ≥ 99.5%), with a total mass of 30g; in an argon atmosphere, lay the above metal raw materials from bottom to top in a crucible according to the melting point from low to high, and then perform arc vacuum melting (vacuum degree of 3×10 -3 Pa), the alloy is completely melted and cooled to form an alloy ingot, the alloy ingot is turned over and smelted repeatedly for 4 times to obtain Zr0.85 Ti 0.15 Ni 1. 2Mn 0.56 V 0.12 Fe 0.12 Precursor;

[0046] (2) In a glove box, the precursor was mechanically crushed into 200 mesh powder using a stainless steel mortar;

[0047] (3) Press Zr 0.85 Ti 0.15 Mg 0.3 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy formula Weigh the precursor powder and Mg powder (purity ≥ 99.5%), mix them evenly manually in a glove box, weigh 20 g of the mixed sample using an analytical balance, and press it into a tablet with a diameter of 13 mm using a powder tablet press;

[0048] (4) The pressed sheet is placed in a stainless steel sealed container in a glove box and filled with argon gas at a pressure of 0.4 MPa; then the pressed sheet is placed in an annealing furnace and sintered for one day at a sintering temperature of 800°C. After the sintering is completed, the pressed sheet is cooled to room temperature with the furnace and then removed, thereby finally obtaining a room temperature reversible hydrogen storage high entropy alloy with a Laves phase structure containing understoichiometric magnesium and a C15 structure.

[0049] Zr 0.85 Ti 0.15 Mg 0.3 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 High entropy alloys consist of a C15 Laves single phase (see Figure 1 :Zr 0.8 5Ti 0.15 Mg 0.3 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 High entropy alloy X-ray diffraction (XRD) test spectrum). Zr 0.85 Ti 0.15 Mg 0.3 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 High entropy alloys can absorb 1.0 wt.% hydrogen at 303 K (see Figure 2 :Zr 0.85 Ti 0.15 Mg 0.3 Ni 1.2 Mn0.56 V 0.12 Fe 0.12 The isothermal hydrogen absorption kinetics of high entropy alloys at 303K) and the complete dehydrogenation at 303K (see Figure 3 :Zr 0.85 Ti 0.15 Mg 0.3 Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Isothermal hydrogen desorption kinetics curve of high entropy alloy at 303K), which indicates that the alloy has the property of reversible hydrogen storage.

[0050] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A room temperature reversible hydrogen storage high entropy alloy with a Laves phase structure and a magnesium-containing C15 structure understoichiometric, characterized in that: The chemical formula of this material is Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 , where x = 0.2~0.4, B / A = 1.4~1.7, Class A elements include Zr, Ti and Mg, and Class B elements include Ni, Mn, V and Fe; The preparation method comprises the following steps: 1) Press Zr first 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy molecular formula Weigh a certain amount of zirconium block, titanium block, vanadium block, iron block, nickel sheet and manganese sheet; in an argon atmosphere, spread the above metal raw materials from bottom to top in a crucible according to the melting point from low to high, and then perform arc vacuum melting at a vacuum degree of (0.3~1)×10-2Pa. After the alloy is completely melted and cooled, an alloy ingot is formed. The alloy ingot is turned over and repeatedly melted 3~4 times to obtain a precursor sample of a hydrogen storage high entropy alloy; 2) In a glove box, the obtained precursor sample was mechanically crushed into 100-300 mesh precursor powder using a stainless steel mortar; 3) Press Zr 0.85 Ti 0.15 Mg x Ni 1.2 Mn 0.56 V 0.12 Fe 0.12 Alloy formula The precursor powder and Mg powder were weighed and mixed evenly manually in a glove box; 4) Weigh a certain amount of the mixed sample using an analytical balance in a glove box, and press it into tablets with a diameter of 10-15 mm using a powder tablet press; 5) Place the pressed sheet in a stainless steel sealed container in a glove box and fill it with argon gas at a pressure of 0.2-0.4 MPa; then place it in an annealing furnace for sintering. After sintering, cool it to room temperature with the furnace and take it out to finally obtain a room temperature reversible hydrogen storage high entropy alloy with a stoichiometric magnesium-containing C15 structure Laves phase.

2. The understoichiometric magnesium-containing C15 Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1, characterized in that: In step 1), the purity of the zirconium block is ≥99.7%, the purity of the titanium block is ≥99.9%, the purity of the vanadium block is ≥99.9%, the purity of the iron block is ≥99.9%, the purity of the nickel sheet is ≥99.5%, and the purity of the manganese sheet is ≥99.5%.

3. The understoichiometric magnesium-containing C15 Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1, characterized in that: In step 1), considering the burning loss of titanium block and manganese sheet during arc melting, 2wt.% titanium block and 5wt.% manganese sheet are additionally added.

4. The understoichiometric magnesium-containing C15 Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1, characterized in that: In step 3), the purity of the Mg powder is ≥99.5%.

5. The understoichiometric magnesium-containing C15 Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1, characterized in that: In step 3), 20 wt.% of Mg powder is additionally added to compensate for the burning loss of Mg powder in the subsequent sintering process.

6. The understoichiometric magnesium-containing C15 Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1, characterized in that: In step 5), the sintering temperature of the sintering process is 750-850° C. and the time is 12-48 hours.

7. Application of the understoichiometric magnesium-containing C15 Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1 in hydrogen storage, characterized in that: Before utilizing the hydrogen storage function of the high entropy alloy, hydrogen absorption and desorption cycles are performed 1 to 2 times at a temperature of 250°C and a pressure of 3.5MPa to obtain the activity of the hydrogen storage high entropy alloy, after which it can be used for hydrogen storage.

Citation Information

Patent Citations

  • Mg-containing room-temperature reversible hydrogen storage high-entropy alloy powder material and preparation method thereof

    CN114275735A